Factors associated with the intention to recommend pertussis vaccination for postpartum women: A survey in Taiwan of obstetrician-gynecologists' knowledge, beliefs, and attitudes - Chuan-Chi Kao; Shang-Yu Huang; Po-Jen Cheng; Sheng-Wen Shaw; Ho-Yen Chueh; Shuenn-Dhy Chang; Te-Yao Hsu; Fu-Tsai Kung; T'sang-T'ang Hsieh (Elsevier, 2012)
Objective: To examine obstetrician-gynecologists' knowledge, beliefs, and attitudes associated with the intention to recommend adult tetanus, reduced diphtheria, and acellular pertussis (Tdap) vaccination to postpartum women. Materials and Methods: A survey instrument was mailed to a total of 2686 members of the Taiwan Association of Obstetrics and Gynecology to assess provider demographic characteristics, occupational information, pertussis knowledge, and beliefs and attitudes about vaccination. The intention to recommend pertussis vaccination to postpartum women was evaluated. Trend chi-square statistics and multivariate logistic models were used to determine variables that were significantly associated with intention to recommend vaccination. Results: Of the 676 surveys returned (25.2%), 510 participants were active in obstetric practice. A statistically significant difference was found in mean ± SD knowledge scores for pertussis disease and pertussis vaccination between obstetrician-gynecologists who intended to recommend and those who did not intend to recommend postpartum Tdap vaccination (disease: 2.99 ± 2.2 vs. 2.31 ± 1.9, respectively, p < .001; vaccination: 2.64 ± 2.2 vs. 1.36 ± 1.8, respectively, p < .001). Obstetrician-gynecologists who were in favor of postpartum Tdap vaccination were more likely to: (1) rate the change in pertussis incidence among adults as increased; (2) rate pertussis disease among newborn infants as highly severe; (3) rate pertussis as highly contagious; and (4) understand the current recommendation of important organizations for protecting infants against pertussis. Conclusion: Our study of obstetrician-gynecologists' attitudes and intentions concerning postpartum Tdap vaccination may be useful in guiding the design of effective perinatal Tdap immunization programs nationwide.